The Issue of Authority Between the National Police Republic of Indonesia and National Narcotics Agency in Handling The Case of Narcotics - Nalapraja, Isya (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 7 No 4 (2018), 2018)
Narcotics eradication is carried out by the National Narcotics Agency based on Law Number 35 of 2009 concerning Narcotics concerning investigations, and narcotics precursor accompanied by wiretapping. In addition to the National Narcotics Agency in Law Number 2 of 2002 concerning the Police that Police Investigators and Civil Servant Investigators have the same authority in combating narcotics. This will lead to a mechanism duet against law enforcement in the framework of eradicating narcotics. This study uses normative legal research methods that depart from the existence of conflicting norms between the authority of the Police and the National Narcotics Agency. Due to the occurrence of authority disputes between the National Narcotics Agency and the Police Force, law enforcement has been ineffective because of the poor coordination of the two institutions and Agency, resulting in competing for authority and causing abuse of authority.